LoRaWAN-based smart water management IoT applications: a review - Enas F. Khairullah; Atheer M. Alghamdi; Mohammad M. Al mojamed; Sherali Zeadally (Journal of Information and Telecommunication)
The Internet of Things (IoT) is one area of the technology field that has grown significantly in recent years. Users can control and monitor IoT systems through smart devices remotely. Many other technologies, such as Zigbee, Wi-Fi, and Bluetooth, are used in IoT systems, however, they consume a lot of energy. Also, these networks are incompatible with battery-powered devices. The Low Power Wide Area Network (LPWAN) was developed to direct this concern and to be a suitable option for longer ranges. A Long Range Wide Area Network (LoRaWAN) is a type of Low Power Wide Area Network (LPWAN) includes battery-powered devices and can communicate in both directions. This study provides comprehensive review of LoRaWAN-based water-management applications. In this survey, we present an overview of LPWAN technologies and compare them. We concentrate on LoRaWAN technology, its architecture, and its main characteristics. Furthermore, we review LoRaWAN-based water applications and classify them into three categories which include: water-quality monitoring applications, water-metering applications, and water-leakage detection applications. We also discuss scalability, simulation, security, and applications of LoRaWAN in water-management systems. Finally, we evaluate the usefulness of LoRaWAN and provide recommendations for researchers to utilize the benefits of LoRaWAN in IoT water-management applications.